ANALYSIS OF FINANCIAL PERFORMANCE OF PT. TELEKOMUNIKASI INDONESIA TBK 2017-2019 - Behuku, Dean Russel Jonathan; Wahda; Taba, Muhammad Idrus (CV. Radja Publika, 2023)
The study aimed to assess the financial performance of PT. Telekomunikasi Indonesia Tbk for the 2017-2019 period based on the Decree of the Minister of State-Owned Enterprises Number: KEP-100/MBU/2002.The data collection technique used was documentation, analyzing financial reports for the specified period. The results indicated that in 2017, the company's financial performance was categorized as